Fraud Pentagon Theory for Detection of Fraudulent Financial Reports: A Preliminary Study in Manufacturing Enterprises in Indonesia - Aziz, Taufiqul; Yuniarti, Rita (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The study aims to test whether the five elements of the Fraud Pentagon are useful in detecting fraud in financial reports. These five elements require proxy variables for analysis and cannot be directly measured. Pressure is measured through external pressure. The nature of industry can be used to measure opportunity. Rationalization is measured by AUDCHANGE. Capability is measured through DCHANGE. Arrogance is measured through the CEO's picture. 23 manufacturing enterprises in the consumer goods category on the IDX were included in the study sample for the 2019–2022 period. The research samples consist of financial statements and annual reports as secondary data. The data was analyzed using logistic regression, and the samples were chosen through purposive sampling. Results showed the significant impact of opportunity, pressure, rationalization, and arrogance on financial report fraud. And for the variable of capability, it showed that it has no effect on fraudulent financial statements.